2013
DOI: 10.1007/978-3-540-93813-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Approaches

Abstract: International audienceThis chapter aims to describe the diversity of participatory approaches in relation to social simulations, with a focus on the interactions between the tools and participants. We consider potential interactions at all stages of the modelling process: conceptual design; implementation; use; and simulation outcome analysis. After reviewing and classifying existing approaches and techniques, we describe two case studies with a focus on the integration of various techniques. The first case st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 53 publications
0
23
0
1
Order By: Relevance
“…With respect to representing actual complex systems using soft system tools, the debate, i.e., simplification versus realism, remains and is understudied (Voinov and Bousquet 2010). Nevertheless, Barreteau et al (2013) suggested the following indicators to assess the quality of the tools used, which we considered in the RPG:…”
Section: Discussionmentioning
confidence: 99%
“…With respect to representing actual complex systems using soft system tools, the debate, i.e., simplification versus realism, remains and is understudied (Voinov and Bousquet 2010). Nevertheless, Barreteau et al (2013) suggested the following indicators to assess the quality of the tools used, which we considered in the RPG:…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the turn towards the language of participation in politics creates an expectation of actual participation. Methods such as participatory modelling, where stakeholders are brought into model development and evaluation, offer powerful tools for bringing together communities and the public into decision-making [4].…”
Section: Sociology and Policymentioning
confidence: 99%
“…Previous reviews about participatory elements in modeling projects (e.g., Barreteau et al 2010;Voinov and Bousquet 2010;Barreteau et al 2013) proposed categorizations and identified functions of participation in modeling projects. In contrast, for instance, Schmitt Olabisi et al (2014) took a different perspective, focusing on the functions of models, and modeling within participatory projects (for example, knowledge integration, addressing types of uncertainties, and generating consensus among stakeholders).…”
Section: Participatory Processmentioning
confidence: 99%
“…The perspective purported by these categorizations is more consistent with the ''truth to power'' idea by participatory methods, indicating that process governance is with the researcher (see also Henriksen et al 2009). Barreteau et al (2013) identified three basic expectations (as they called it) of participatory approaches in modeling. First, one expects to upgrade the quality of a simulation model.…”
Section: Functional-dynamic Perspective On Participatory Processesmentioning
confidence: 99%
See 1 more Smart Citation